Aktivitas Antibakteri Sediaan Gel dari Fraksi Aktif Daun Sintrong (Crassocephalum Crepidioides (Benth) S Moore) - Muharni Saputri; Vriezka Mierza (Forum Kerjasama Pendidikan Tinggi (FKPT), 2020)
Indonesia is a tropical country that allows bacteria to easily grow and develop, especially in the skin. The drugs used are very diverse, generally from corticosteroids, which have side effects. This encourages the need for research on antimicrobial drugs from natural ingredients such as herbs that have high potency and relatively low side effects. Sintrong plants (Crassocephalum crepidioides (Benth.) S. Moore) are found in Parmeraan Village, Dolok District, North Padang Lawas Regency, North Sumatra Province. This plant is thought to contain alkaloid compounds and tannins as antimicrobials. This research method is an experimental study with the maceration method of ethanol extract and fractionation of n-hexane, ethyl acetate, phytochemical screening, making topical gels 20%, 10%, and 5% with parameters of pH, homogeneity, viscosity, dispersibility and adhesion as well as Antibacterial test against pure cultured bacteria using agar diffusion method using metal buffer, the bacteria used were gram-positive bacteria (Staphylococcus aureus ATCC 29737) and gram-negative bacteria (Escherichia coli ATCC 10536). The results showed that the ethanol extract of Sintrong leaves can be formulated in the form of a gel. The results of the evaluation that have been carried out on the methanol extract gel of Sintrong leaves show that the preparation has met the gel requirements. The formula that has the best antibacterial activity is Formula 1 which provides an inhibitory diameter of 17.10 mm and 18.75 mm for Escherichia coli and Staphylococcus aureus bacteria.